Isoflurane Damages the Developing Brain of Mice and Induces Subsequent Learning and Memory Deficits through FASL-FAS Signaling. (1st November 2015) - Yi, Xiuwen; Cai, Yirong; Li, Wenxian
Abstract : Background . Isoflurane disrupts brain development of neonatal mice, but its mechanism is unclear. We explored whether isoflurane damaged developing hippocampi through FASL-FAS signaling pathway, which is a well-known pathway of apoptosis. Method . Wild type and FAS- or FASL-gene-knockout mice aged 7 days were exposed to either isoflurane or pure oxygen. We used western blotting to study expressions of caspase-3, FAS (CD95), and FAS ligand (FASL or CD95L) proteins, TUNEL staining to count apoptotic cells in hippocampus, and Morris water maze (MWM) to evaluate learning and memory. Result . Isoflurane increased expression of FAS and FASL proteins in wild type mice. Compared to isoflurane-treated FAS- and FASL-knockout mice, isoflurane-treated wild type mice had higher expression of caspase-3 and more TUNEL-positive hippocampal cells. Expression of caspase-3 in wild isoflurane group, wild control group, FAS/FASL-gene-knockout control group, and FAS/FASL-gene-knockout isoflurane group showed FAS or FASL gene knockout might attenuate increase of caspase-3 caused by isoflurane. MWM showed isoflurane treatment of wild type mice significantly prolonged escape latency and reduced platform crossing times compared with gene-knockout isoflurane-treated groups. Conclusion . Isoflurane induces apoptosis in developing hippocampi of wild type mice but not in FAS- and FASL-knockout mice and damages brain development through FASL-FAS signaling.